Examining The Mediating Role of Negative Dyadic Coping between Parental Stress and Child Externalizing Behavior - Aretha Ever Ulitua; Naomi Soetikno (Jurnal Psikiatri Surabaya, 2026)
Introduction: Behavioral problems have become a concern that often occurs in children, especially in elementary schools, and have not been appropriately handled. Behavioral problems that often occurs in children is externalizing behavior. One of the factors that can affect externalizing behavior is the character of parenting seen from parental stress. This research aims to know precisely how the role of negative dyadic coping as a mediator influences the relationship between parental stress and externalizing behavior in the middle to late childhood. Methods: This research method is a quantitative correlational research non-experiment conducted on 458 parents (229 fathers and 229 mothers). The participants characteristic is parents with children with externalizing behavior aged 6-12 years old in elementary school. The scale used in the study is SDQ (Strength and Difficulties Questionnaire), PSS (Parental Stress Scale), and DCI (Dyadic Coping Inventory). Results: The results showed that children’s externalizing conduct was mostly moderate. Parental stress among both fathers and mothers fell into the moderate group, as did total dyadic coping and its aspects. Mediation analysis with PROCESS Hayes found that negative dyadic coping strongly mediated the association with parental stress and child externalizing behaviour (indirect impact = 0.0889; LLCI = 0.0172; ULCI = 0.0529, indicating a significant indirect influence. A gender comparison analysis revealed that boys displayed markedly elevated levels of externalizing behaviour compared to girls (t= 2.378, p<0.05). Conclusion: This research shows negative dyadic coping mediated the relationship between parental stress and externalizing behavior with a 0,0889 effect.